Evolutionary history of arbuscular mycorrhizal fungi and genomic signatures of obligate symbiosis - Rosling, Anna (Uppsala University, 2024)
- Suppl datafile 1 MCGC_Shadi_10_21-with analysis 2023

This file contains the analysis and results presence / absence for so called Missing Core Glomeromycota Genes (MCGC).

- Suppl datafile 2 CAZyme_22_10-31

This file contains the gene family counts for CAZyme families, as well as an analysis of families previously identified as Plant Cell Wall Degrading Enzymes (PCWDE) and familes selected for Figure 2 in the manuscript.

Files with summary statistics from comparative genomic analysis based on Funnanotate and used for the anlaysis in the paper: busco-complete-summary-Shadis-genomes; CAZyme.all.results; CAZyme.summar.results; MEROPS.all.results; MEROPS.summary.results; pfam.results; signalp

Ancestral reconstruction trees for CAZyme families and Peptideases with significant changes are available in the files Cazyme_trees and plots_peptidases_pdf.
Keywords: Evolutionary ecology; Microbial taxonomy; Phylogeny and comparative analysis; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi